Process mineralogy of a lithium enriched pegmatite combining mineral separation and SEM based automated mineralogy. - Timich, Marco (2021)
Brines located in Chile and Argentina are the main lithium reserve, however over 50% of lithium production comes from pegmatites distributed around the world. With the increase in lithium demand driven by its applications in energy storage technologies, pegmatite deposits become increasingly economically viable. Lithium\'s reserve in Brazil is found exclusively in pegmatites and accounts for less than 1% of global reserves, but a recent study indicates that Brazil can reach up to 8% of global reserves. This paper reports process mineralogy studies performed in 10 samples from a lithium pegmatite deposit from southeastern of Minas Gerais state in Brazil. Samples characterization were carried out combining heavy liquid separation and X-ray based automated mineralogy using Mineral Liberation Analyzer system (MLA) allied to XRF, ICP-OES, XRD and LA-ICPMS. Results showed that besides spodumene (8.0 wt% Li2O), there are other lithium-bearing minerals, as muscovite (0.5 wt% Li2O) and lepidolite (3.1 wt% Li2O). The characterization of the spodumene (d=3.11) concentrate obtained by heavy liquid separation (d=2.95) revealed that samples present two main trends a) -samples with low lithium distribution in the sink product (~44%) with higher Li2O grade (~6.5 wt%) and b) -samples with higher lithium distribution in the sink product (58%) with lower Li2O content (~4.9 wt%). Lower lithium distribution in sink product is associated with higher modal content of micas since they carry lithium to the floated product. Lower lithium grade is related to the presence of iron-bearing minerals (e.g., epidote and amphibole), since they report to the sink product and do not contain Li. The liberation degree of spodumene is high and similar in all samples, therefore it did not influence distribution results. This work highlights the use of scanning electron microscopy (SEM) based automated mineralogy combined with other techniques in process mineralogy studies to guide mineral processing. Besides mineralogy and liberation characteristic, especially important was identifying lithium-bearing minerals and determining lithium\'s deportment.